The Role of Growth Factors in Bioactive Coatings - Dragana Bjelić; Matjaž Finšgar (Pharmaceutics, 2021)
With increasing obesity and an ageing population, health complications are also on the rise, such as the need to replace a joint with an artificial one. In both humans and animals, the integration of the implant is crucial, and bioactive coatings play an important role in bone tissue engineering. Since bone tissue engineering is about designing an implant that maximally mimics natural bone and is accepted by the tissue, the search for optimal materials and therapeutic agents and their concentrations is increasing. The incorporation of growth factors (GFs) in a bioactive coating represents a novel approach in bone tissue engineering, in which osteoinduction is enhanced in order to create the optimal conditions for the bone healing process, which crucially affects implant fixation. For the application of GFs in coatings and their implementation in clinical practice, factors such as the choice of one or more GFs, their concentration, the coating material, the method of incorporation, and the implant material must be considered to achieve the desired controlled release. Therefore, the avoidance of revision surgery also depends on the success of the design of the most appropriate bioactive coating. This overview considers the integration of the most common GFs that have been investigated in in vitro and in vivo studies, as well as in human clinical trials, with the aim of applying them in bioactive coatings. An overview of the main therapeutic agents that can stimulate cells to express the GFs necessary for bone tissue development is also provided. The main objective is to present the advantages and disadvantages of the GFs that have shown promise for inclusion in bioactive coatings according to the results of numerous studies.